Maqashidi Interpretation of Q.S. Al-Baqarah [2]: 208 Regarding Kaffah Islam - Zihan Nur Rahma; Moh. Abdulloh Hilmi (Spiritus: Religious Studies and Education Journal, 2023)
This article discusses Tafsir Maqashidi regarding "Islam Kaffah" and its impact on democracy in Indonesia. "Islam Kaffah," as a reformist movement within Islam emphasizing textual aspects, often sparks controversy within the Indonesian democracy context. This study employs Tafsir Maqashidi to analyze Q.S. al-Baqarah [2]: 208. Three analytical phases are employed: firstly, the interpretation of the verse to unravel its meaning; secondly, linguistic analysis to comprehend the content of the verse; thirdly, the interpretation of "wasilah" (cause) and "ghayah" (objective) in Q.S. al-Baqarah [2]: 208, resulting in an understanding of the "maqashid al-Qur'an." The findings reveal that "Islam Kaffah" refers to a comprehensive Islam. Micro Asbab an-Nuzul is linked to the declaration of faith by Abdullah bin Salam and his companions and the law of Moses. On a macro level, Asbab an-Nuzul is associated with the conflicts in Medina between the Aus and Khazraj tribes and the Qinuqa, bani Nadzir, and Quraidha tribes. The "Maqashid" of Q.S. al-Baqarah [2]: 208 calls on the community to implement "Islam Kaffah" with a primary focus on spreading peace, following the example of Prophet Muhammad SAW. Maqashidi interpretation reinforces the idea that "Islam Kaffah" should promote peace within society.